2011
DOI: 10.1080/00028487.2011.618356
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Migrating Atlantic Salmon Smolts through the Penobscot River, Maine: a Prerestoration Assessment

Abstract: Survival, distribution, and behavior of hatchery (n = 493) and naturally reared (n = 133) smolts of Atlantic salmon Salmo salar migrating through the Penobscot River and estuary in Maine were evaluated with acoustic telemetry in 2005 and 2006. Survival and use of a secondary migration path (the Stillwater Branch) were estimated with a multistate mark–recapture model. Higher rates of mortality per kilometer (range = 0.01–0.22) were observed near release sites and within reaches that contained three particular d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
72
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(72 citation statements)
references
References 33 publications
0
72
0
Order By: Relevance
“…No mortality was observed in any of those fish. Previous studies observed elevated mortality immediately following release (up to 50% in wild smolts but generally less than 5% in hatchery-reared fish) associated with the handling, transport, and release of acoustically tagged smolts in the Penobscot River (Holbrook et al 2011). All smolts used for analyses in the present study were released a minimum of 50 km above the head of tide (rkm 45), so we assumed that residual effects of tagging were minimal during estuary passage.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…No mortality was observed in any of those fish. Previous studies observed elevated mortality immediately following release (up to 50% in wild smolts but generally less than 5% in hatchery-reared fish) associated with the handling, transport, and release of acoustically tagged smolts in the Penobscot River (Holbrook et al 2011). All smolts used for analyses in the present study were released a minimum of 50 km above the head of tide (rkm 45), so we assumed that residual effects of tagging were minimal during estuary passage.…”
Section: Methodsmentioning
confidence: 99%
“…The removal of Great Works and Veazie dams will likely increase smolt survival in the Penobscot River estuary by reducing dam-related mortality in the estuary (Figure 5), even though these dams resulted in little acute mortality during freshwater smolt migration (Holbrook et al 2011;Stich et al 2014). Indeed, the indirect, dam-related estuary mortality resulting from each of these structures (about 6%; Figure 5) was greater than the direct mortality incurred during passage (0-1%) of the facilities (Holbrook et al 2011;Stich et al 2014).…”
Section: Conservation and Management Implicationsmentioning
confidence: 99%
See 3 more Smart Citations